Diversity, Abundance, and Potential Activity of Nitrifying and Nitrate-Reducing Microbial Assemblages in a Subglacial Ecosystem - Boyd, Eric S. (American Society for Microbiology, 2011)

(untitled)
Subglacial sediments sampled from beneath Robertson Glacier (RG), Alberta, Canada, were shown to harbor diverse assemblages of potential nitrifiers, nitrate reducers, and diazotrophs, as assessed by amoA, narG, and nifH gene biomarker diversity. Although archaeal amoA genes were detected, they were less abundant and less diverse than bacterial amoA, suggesting that bacteria are the predominant nitrifiers in RG sediments. Maximum nitrification and nitrate reduction rates in microcosms incubated at 4°C were 280 and 18.5 nmol of N per g of dry weight sediment per day, respectively, indicating the potential for these processes to occur in situ. Geochemical analyses of subglacial sediment pore waters and bulk subglacial meltwaters revealed low concentrations of inorganic and organic nitrogen compounds. These data, when coupled with a C/N atomic ratio of dissolved organic matter in subglacial pore waters of ∼210, indicate that the sediment communities are N limited. This may reflect the combined biological activities of organic N mineralization, nitrification, and nitrate reduction. Despite evidence of N limitation and the detection of nifH, we were unable to detect biological nitrogen fixation activity in subglacial sediments. Collectively, the results presented here suggest a role for nitrification and nitrate reduction in sustaining microbial life in subglacial environments. Considering that ice currently covers 11% of the terrestrial landmass and has covered significantly greater portions of Earth at times in the past, the demonstration of nitrification and nitrate reduction in subglacial environments furthers our understanding of the potential for these environments to contribute to global biogeochemical cycles on glacial-interglacial timescales.